IbM PEMBINAAN KELOMPOK IBU HAMIL YANG MENDERITA ANEMIA DI WILAYAH KERJA PUSKESMAS GANDUS KOTA PALEMBANG - Mardiana Mardiana; Hana Yuniarti (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT, POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN PALEMBANG, 2020)
Nutritional anemia is the most common public health problem, which can lead to a decrease in human quality. The needs of pregnant women for iron, in addition to covering basal losses, also for the need for the formation of red blood cells that increase in number, and also for the needs of the placenta and fetus in the womb. To prevent anemia on an ongoing basis, it is cheap and affordable. The alternative is to consume enough green vegetables, beans, grains and fruits, so that the food consumed is quite diverse, both in quantity and in quality.It is hoped that with the Community Service at an advanced stage (Guidance) by the lecturer of the D III Nutrition Study Program in the working area of ​​the Gandus Health Center, a truly useful and educative way to prevent anemia is to provide nutrition education through demonstrations of processing food with basic ingredients of cassava, tempeh and green vegetables. The results of the implementation of Community Service at an advanced stage (Guidance) by Lecturers of the D III Nutrition Study Program, it was found that an increase in the Hb level of anemic pregnant women, which previously had an average Hb level of < 8.8 mg/dl after coaching, increased by 11.6 mg /dl and furthermore, from the results of the cooking demo, 2 types of dishes made from local ingredients are presented in the form of healthy porridge and Tempe Nagget.